Pen-sei: a implantação do processo eletrônico nacional através do sistema eletrônico de informações na Universidade Federal de Juiz de Fora - Costa, Arlene Xavier Santos (2020)
The present research has as main objective analyze the public policy of National Electronic Process (PEN) - of the Federal Government, due to the implantation of the Electronic Information System - SEI - in the Universidade Federal de Juiz de Fora (UFJF) by the perspective of the archival management principles applied to digital records. This is a case study in which we privilege the methodology of documentary research in primary sources with the outline of an exploratory and also descriptive study, given the contemporary nature of the theme. The data were collected on websites of the Federal Government and UFJF related to public information and governance policies, federal laws and decrees, norms of the National Archives and internal regulations of UFJF. Based on these data, we contextualize the national scenario for the implementation of the PEN, with an emphasis on Higher Education Institutions (IES) and analyze the lack of connection between public information policies and public archive policies in Brazil through the invisibility of archives bodies and entities in the implementation policy related to the agenda. As a result, we present a critical analysis of SEI-UFJF from the perspective of archival management. As a contribution, at the end we present suggestions for improvements to the process of implementing the system at the University and for implementing best practices in archival management of digital records.